Causal explanations for patient engagement with primary care services in Saudi Arabia: a realist review protocol - Alghamdi, A; Abrams, R; Bailey, JV; Alves, P; Park, S (BMJ Publishing Group, 2022)
Introduction Saudi Arabia (SA) has a rapidly developing universal healthcare system which is maturing from its hospital focused origins. However, health service usage suggests that up to 65% of the cases seen in emergency departments were classified as non-urgent and could have been appropriately managed in primary healthcare (PHC) settings. Primary care development in SA has lagged behind secondary care, and evidence suggests that Saudi citizens are currently ambivalent or dissatisfied with their PHC services. Previous research has focused on the quality and patient satisfaction of PHC services in SA. Yet, uncertainty still exists about causal explanations for patient engagement with PHC services and what refinements are needed for PHC. Less attention has been paid to how patient engagement strategies might work differently, which is increasingly recognised as important in PHC services. The aim of this review is to understand the causal explanations for patient engagement with PHC and to generate theory of how the intended outcome of patient engagement with PHC in SA might be achieved through identified contexts and mechanisms.